2021
DOI: 10.1007/s13555-021-00500-4
|View full text |Cite
|
Sign up to set email alerts
|

Tolerability of and Adherence to Topical Treatments in Atopic Dermatitis: A Narrative Review

Abstract: Atopic dermatitis (AD) is a common, chronic inflammatory skin disease that oftentimes requires complex therapy. Poor adherence is a major barrier to AD treatment success. An interspecialty, virtual roundtable panel was held, through which clinical dermatologists, allergists, and behavioral and social psychologists discussed AD management and adherence. Relevant literature was reviewed, and the content of this article was organized based on the roundtable discussion. Current guidelines for AD treatment include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Studies have demonstrated that product efficacy, safety and convenience all play a key role in ensuring the highest possible adherence to therapy by patients [ 1 4 , 47 ]. Patients with psoriasis and atopic dermatitis have been reported to miss up to around 70% of planned topical applications when the treatment period extends to several weeks, leading to suboptimal treatment outcomes, reduced quality of life and increased healthcare costs [ 1 , 13 , 48 , 49 ]. Patients generally prefer light, moisturizing, non-greasy and quickly absorbed vehicles for reasons of ease of application and aesthetic acceptability [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that product efficacy, safety and convenience all play a key role in ensuring the highest possible adherence to therapy by patients [ 1 4 , 47 ]. Patients with psoriasis and atopic dermatitis have been reported to miss up to around 70% of planned topical applications when the treatment period extends to several weeks, leading to suboptimal treatment outcomes, reduced quality of life and increased healthcare costs [ 1 , 13 , 48 , 49 ]. Patients generally prefer light, moisturizing, non-greasy and quickly absorbed vehicles for reasons of ease of application and aesthetic acceptability [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Proaktivno doziranje: održavanje postignutog efekta i nakon sanacije akutne egzacerbacije hronične dermatoze (najčešće psorijaza ili atopijski dermatitis) primenom kortikosteroidnog preparata 2 puta nedeljno još neki period, do prestanka korišćenja kortikosteroida. Može se kombinovati sa drugim aktivnim medikamentima (kalcineurin inhibitorima ili kalcipotriolom) [17][18] .…”
Section: Strategije Optimizacije Hronične Topikalne Kortikosteroidne ...unclassified
“…Some trials supply TCS directly to participants [ 14 , 17 ], which minimizes barriers to use. In such trials, participants may use TCS more consistently and in greater amounts than they would in the real-world where a prescription is typically required [ 28 ]. Other trials do not supply TCS and require participants to obtain new TCS prescriptions [ 10 , 13 ].…”
Section: Key Clinical Trial Parameters That Impact Interpretation Of Efficacy Outcomesmentioning
confidence: 99%